G20, Infrastructure Tourism, and Renewable Energy Tourism - Muhammad Ikhsan Setiawan; Agus Sukoco; Dahlan Abdullah; Cut Ita Erliana; Paisal Halim; Syamsiah Badruddin; Hery Budiyanto (LPPM of NAROTAMA UNIVERSITY, 2023)
The tourism industry has made an enormous difference in terms of jobs, foreign exchange, and the building up of infrastructure. On the other hand, many infrastructures can make natural places look less attractive, which calls for sustainable tourism. It's vital to help small businesses get money through excellent digital infrastructure and to use public fiscal tools to ensure that natural resources are used sustainably. Infrastructure tourism was used as the title, abstract, and keywords in 6,377 documents from 1968 to 2023 found in the scopus.com database. It also shows 704 papers with the title, abstract, and article keyword